Detection of Faint BLR Components in the Starburst/Seyfert Galaxy NGC 6221 and Measure of the Central BH Mass - La Franca, Fabio; Onori, Francesca; Ricci, Federica; Bianchi, Stefano; Marconi, Alessandro; Sani, Eleonora; Vignali, Cristian (Frontiers in Astronomy and Space Sciences, 2016)
In the last decade, using single epoch virial based techniques in the optical band, it has been possible to measure the central black hole mass on large type 1 Active Galactic Nuclei (AGN) samples. However, these measurements use the width of the broad line region (BLR) as a proxy of the virial velocities and are therefore difficult to be carried out on those obscured (type 2) or low luminosity AGN where the nuclear component does not dominate in the optical. Here we present the optical and near infrared spectrum of the starburst/Seyfert galaxy NGC 6221, observed with X-shooter/VLT. Previous observations of NGC 6221 in the X-ray band shows an absorbed (NH=8.5±0.4×1021cm-2) spectrum typical of a type 2 AGN with luminosity log(L14−195/erg s−1) = 42.05, while in the optical band its spectrum is typical of a reddened (AV = 3) starburst. Our deep X-shooter/VLT observations have allowed us to detect faint broad emission in the Hα, HeI, and Paβ lines (FWHM ~1400–2300 km s−1) confirming previous studies indicating that NGC 6221 is a reddened starbust galaxy which hosts an AGN. We use the measure of the broad components to provide a first estimate of its central black hole mass (MBH=106.6±0.3M⊙, λEdd = 0.01−0.03), obtained using recently calibrated virial relations suitable for moderately obscured (NH < 1024 cm−2) AGN.